Mental Health Correlates of Probable Posttraumatic Stress Disorder, Probable Alcohol Use Disorder, and Their Co-Occurrence among Firefighters. Issue 2 (March 2022) - Zegel, Maya; Lebeaut, Antoine; Healy, Nathaniel; Tran, Jana K.; Vujanovic, Anka A.
Firefighters demonstrate high rates of posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD). Research has yet to compare how these diagnoses and their co-occurrence relate to firefighter mental health. This study evaluated trauma load, PTSD, alcohol use, depression, sleep, suicide risk, anger, and occupational stress across four discrete groups of firefighters ( N  = 660): (1) trauma-exposed only ( n  = 471), (2) probable PTSD-only ( n  = 36), (3) probable AUD-only ( n  = 125), and (4) probable PTSD-AUD ( n  = 28). Firefighters completed an online survey. Firefighters with probable PTSD-AUD demonstrated higher scores on all criterion variables, except trauma load, compared to firefighters with probable AUD-only or trauma-only. Firefighters with probable PTSD-AUD and probable PTSD-only reported similar levels of all indices, except alcohol use severity and suicide risk, which were higher among the probable PTSD-AUD group. Results provide preliminary empirical evidence of the deleterious impact of PTSD-AUD comorbidity among firefighters.